PENGARUH SIZE, WEALTH, LEVERAGE, DAN BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH (Studi Kasus di Kabupaten Karanganyar) - Pipit Nur Fitasari; Kun Ismawati (Universitas Sahid Surakarta, 2020)
This research aims to know size, wealth, leverage, and capital expenditure influence to the government financial performance in Karanganyar district both in Partial or simultaneous. Hypothesis suspected that size, wealth, and capital expenditure have a positive and significant influence to the government financial performance in Karanganyar district, whereas leverage has negative effect but not significant to the government financial performance in Karanganyar district.This research is a quantitative research with secondary data collected from Regions Financial Body (BKD) Karanganyar district in the form of balance sheetand financial statement in period research years 2010-2017. Analysis of data used in the research are multiple linear regression test, t test, F test, and coefficientdetermination test. Results data analysis shows that leverage and capital expenditure takes a negative and not significant effect to the government financial performance in Karanganyar district years 2010-2017, whereas size and wealth have positive and significant effect to the government financial performance in Karanganyar district years 2010-2017.